The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1038/s41598-017-09276-0
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the genetic cause of a consanguineous family with unilateral coloboma and retinoschisis: expanding the phenotypic variability of RAX mutations

Abstract: Ocular coloboma is a common eye malformation arising from incomplete closure of the human optic fissure during development. Multiple genetic mutations contribute to the disease process, showing extensive genetic heterogeneity and complexity of coloboma spectrum diseases. In this study, we aimed to unravel the genetic cause of a consanguineous family with unilateral coloboma and retinoschisis. The subjects were recruited and underwent specialized ophthalmologic clinical examination. A combination of whole exome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This presumably allowed for some residual activity for the RAX protein. Their eye phenotype was very severe (bilateral anophthalmia) except for the patient reported by Huang et al (22), a 14-year-old boy, who had a later developmental eye anomaly (coloboma) and was homozygous for a possibly damaging missense mutation (PolyPhen2 score, 0.873). The remaining patients had a severe and early developmental eye malformation.…”
Section: Discussionmentioning
confidence: 97%
“…This presumably allowed for some residual activity for the RAX protein. Their eye phenotype was very severe (bilateral anophthalmia) except for the patient reported by Huang et al (22), a 14-year-old boy, who had a later developmental eye anomaly (coloboma) and was homozygous for a possibly damaging missense mutation (PolyPhen2 score, 0.873). The remaining patients had a severe and early developmental eye malformation.…”
Section: Discussionmentioning
confidence: 97%
“…Biallelic mutations have been identified in 7 families with a bilateral and severe ocular A/M phenotype (Abouzeid et al 2012;Chassaing et al 2014;Lequeux et al 2008;Voronina et al 2004) and in 1 family with isolated unilateral coloboma and retinoschisis (Huang et al 2017). These mutations are of varying nature (missense, nonsense, frameshift and splicing mutations, and a gene deletion), but all act through a "loss-of-function" mechanism.…”
Section: Rax (Retina and Anterior Neural Fold Homeobox)mentioning
confidence: 99%
“…In humans, mutations in several transcription factor genes have been reported to cause disruption of vertebrate eye development or maintenance. [ 10 11 12 13 14 15 27 28 29 30 31 32 ] This led to the hypothesis that polymorphisms in these genes may also predispose towards the risk of congenital eye disorders. In our previous studies on mutation screening in candidate genes for congenital cataract and microphthalmia, we observed that the frequency of two polymorphisms FOXE3 -p.Ala170Ala and PITX3 -p.Ile95Ile was higher in congenital cataract and microphthalmia cases as compared to controls.…”
Section: Discussionmentioning
confidence: 99%